Kepemimpinan Pengajaran dan Pelaksanaan Inovasi Kurikulum di Sekolah Menengah Daerah Kota Setar, Kedah - Samsor, Sahdan (2003)
The purpose of the research is to look into the relationship between the principal’s instructional leadership with the implementation of curriculum innovation in secondary school in the district of Kota Setar, Kedah. This research was held in two category school, the school in town center and the outskirts of the town. The data for this research is compile by using a set of questionnaire from 120 respondents, which are teachers selected at random from the two category school. The principal’s instructional leadership was determined by using the Principal Instructional Leadership questionnaire whereas the Implementation of Curriculum Innovation questionnaire was used to measure the curriculum innovation implemented in secondary school. Two statistic methods have been used to analyst the data in answering the research questions. Those are the descriptive method, which involved the frequency, percentage, min and standard deviations while the inference method, which involved the Pearson’s correlatio-n and the t- test. The result of the research shows that the degree of instructional leadership by the principal either from the school in town center or the school outskirts of the town is high. Research also shows that only one instructional leadership characteristic that is the charisma has its significant differences between the school town center and the school outskits of the town. It also shows that there is no significant relationship between the principal’s instructional leadership and the intellectual stimulation, individual consideration and inspirational motivation with the implementation of curriculum innovation in school merely moderate in term of relationship strength. Overall, the research proved that is a significant relationship between the principal’s instructional leadership and the charisma characteristic, intellectual stimulation, individual consideration and the inspirational motivation with the implementation of curriculum innovation in secondary school. Research suggested that the related authorities such as the district education office, the state education depatiment, the education ministry and the higher education institutions will plan and implement a special programme to train the principal in instructional leadership. The sufficient knowledge and skills regarding the curriculum innovation should be exposed to all principals and teachers in school.